2021
DOI: 10.1002/anie.202107861
|View full text |Cite
|
Sign up to set email alerts
|

Insight on the Order of Regioselective Ultrafast Formation of Disulfide Bonds in (Antimicrobial) Peptides and Miniproteins

Abstract: Disulfide-rich peptides and proteins are among the most fascinating bioactive molecules.T he difficulties associated with the preparation of these targets have prompted the development of various chemical strategies.N evertheless,t he production of these targets remains very challenging or elusive. Recently,w ei ntroduced as trategy for one-pot disulfide bond formation, tackling most of the previous limitations.However, the effect of the order of oxidation remained an underexplored issue.Herein we report on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…Based on our previous work, residues 9, 10, and 11 on LvIA were identified as promising positions to investigate selectivity-altering mutations . Thus, using a recently developed ultrafast de novo synthesis strategy, , we prepared 0.6 to 1.5 mg of wild-type (WT) LvIA, three previously tested controls (D9A, D10A, D11A), and six new α-CTX mutants (N9Y, N9Q, V10Q, V10L, D11R, D11N) (Figure and Synthesis Supplement: Synthetic Methods, HPLC, and MS Spectra) and determined their potencies for α3β2 and α3β4 nAChRs by two-electrode voltage clamp electrophysiology (TEVC) (Table and Figure ). Consistent with the previously reported IC 50 values and 18-fold selectivity, we found that WT LvIA was 25-fold more selective for the α3β2 nAChR over the α3β4 nAChR (Table and Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Based on our previous work, residues 9, 10, and 11 on LvIA were identified as promising positions to investigate selectivity-altering mutations . Thus, using a recently developed ultrafast de novo synthesis strategy, , we prepared 0.6 to 1.5 mg of wild-type (WT) LvIA, three previously tested controls (D9A, D10A, D11A), and six new α-CTX mutants (N9Y, N9Q, V10Q, V10L, D11R, D11N) (Figure and Synthesis Supplement: Synthetic Methods, HPLC, and MS Spectra) and determined their potencies for α3β2 and α3β4 nAChRs by two-electrode voltage clamp electrophysiology (TEVC) (Table and Figure ). Consistent with the previously reported IC 50 values and 18-fold selectivity, we found that WT LvIA was 25-fold more selective for the α3β2 nAChR over the α3β4 nAChR (Table and Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Notably, forming the second disulfide bond was carried out in acidic media, in which a fast reaction rate was achieved, and the disulfide reshuffling could be inhibited. 5 A linear α-conotoxin SI bearing two free Cys residues (Cys2 and Cys7) and two Cys residues with side chains protected by Acm (Cys3 and Cys13) was first treated with MetSeO in a buffer of pH 7.0, followed by treating with HBr to directly generate 1 with two disulfides (Figure 1 and Figures S1 and S2). Therefore, the two Acm protection groups were successfully deprotected by MetSeO assisted by Br − and H + .…”
Section: ■ Introductionmentioning
confidence: 99%
“…Cysteine (Cys) side chains protected by acetamidomethyl (Acm), 1,3-thiazolidine (Thz), and t -butyl ( t Bu) were often used for chemical syntheses of proteins and of peptide multiple disulfide bonds through stepwise deprotections followed by oxidations . Recently, one-pot regioselectively synthetic approaches of multiple disulfide bonds in peptides were developed by the Brik group by use of these protected Cys, being more efficient in the synthesis of such kind of peptides. ,,, Deprotection of the Cys protecting groups can be achieved using a variety of reagents such as Hg­(II), Ag­(I), Tl­(III), Pd­(II), Pt­(IV), Cu­(II), I 2 , 2,2 ′ -dithiobis­(5-nitropyridine) (DTNP), triisopropylsilane (TIS), triethylsilane (TES), 2,2-dipyridyl disulfide (DPDS), and 2,2′-dipyridyl diselenide, affording cysteine or cystine peptides. However, some drawbacks still remain, including the oxidation of tryptophan and methionine residues in the peptides, harsh reaction conditions, and over-oxidations, which give some limits for their applications in the formation of disulfide bonds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, a large number of disulfide-containing peptides are in clinical trials, and the Food and Drug Administration (FDA) has already approved some . Notable efforts have been dedicated to their chemical synthesis, especially establishing regioselective disulfide connection in a disulfide-rich peptide, , yet the developed methods are relatively popular in the solution phase. Single disulfide-driven peptide macrocyclization is well established in the solution phase using diverse reagents .…”
mentioning
confidence: 99%